NPCR(%), average of 20 times. - Bin Yang (103252) (2025)
As an efficient technique to protect image content from unauthorized access, image encryption has been a hot spot in recent studies. Among various schemes of image encryption, those that utilize hyperchaotic systems and deoxyribonucleicacid (DNA) computing are promising. In this paper, complementary rules of eight-base DNA computing are proposed, whose number is 5040, whereas the number of complementary rules of traditional four-base DNA is only 6. Hence, complementary rules of eight-base DNA can introduce larger flexibility and complexity into image encryption. In addition, a new extended Zigzag transform is proposed, which can generate a large number of Zigzag-like paths. By combining a four-dimensional (4D) hyperchaotic system, complementary rules of eight-base DNA and the new extended Zigzag transform, a new hyperchaotic encryption scheme for color images called EDCREZT is proposed. During the encryption procedure of EDCREZT, a plaintext color image will pass through five steps: pixel-level permutation, dynamic DNA encoding, DNA-level permutation by the new extended Zigzag transform, two-round DNA-level diffusion by the proposed complementary rules, and dynamic DNA decoding, then the cipher image is obtained. Extensive experiments have been conducted, and the results show EDCREZT possesses satisfying capability against typical attacks.